Comparing assessment tools for detecting undernutrition in patients with liver cirrhosis. (February 2018) - McFarlane, M.; Hammond, C.; Roper, T.; Mukarati, J.; Ford, R.; Burrell, J.; Gordon, V.; Burch, N.
Summary: Background and aims: Undernutrition in cirrhotic patients is often poorly recognised until late-stages. The current UK screening tool, the Malnutrition Universal Screening Tool, can miss undernutrition in patients with ascites/fluid retention. A 6-question Liver Disease Undernutrition Screening Tool (LDUST) has been developed in America. Methods: We sought to compare LDUST with MUST in the detection of undernutrition in 50 inpatients and 50 outpatients with liver cirrhosis in a secondary care setting. This was then validated by a dietitian assessment. Results: Similar patient demographics and liver disease aetiologies were found in the two cohorts. Mean Child-Pugh scores were higher for inpatients, 8.3 (SD 1.9) vs 5.9 (SD 1.2). LDUST detected undernutrition in 45/50 inpatients (90%) and 34/50 outpatients (68%). MUST scores ≥2 were present in 19/50 (38%) inpatients and 9/50 (18%) outpatients. In those with a MUST score <2, LDUST detected undernutrition in 26/31 (84%) inpatients and 27/41 (66%) outpatients. 26 inpatients had undernutrition using LDUST but had a MUST score <2, 20 (76%) of these were deemed to be undernourished by dietetics assessment. LDUST was mostly completed independently or with minimal assistance (80% inpatients, 100% outpatients), with mean completion times of 4 and 3 min for in- and outpatients respectively. Conclusion: LDUST is a quick and easy screening tool, which appears better able than MUST to detect undernutrition in cirrhotic patients, including undernutrition missed by MUST. Importantly the tool was validated against dietitian assessments. The high rates of undernutrition among cirrhotic inpatients suggest that screening this cohort is unnecessary, and instead all should undergo dietitian review, with LDUST utilised in an outpatient setting.